2017
DOI: 10.1111/cgf.13295
|View full text |Cite
|
Sign up to set email alerts
|

Olfaction and Selective Rendering

Abstract: Accurate simulation of all the senses in virtual environments is a computationally expensive task. Visual saliency models have been used to improve computational performance for rendered content, but this is insufficient for multi‐modal environments. This paper considers cross‐modal perception and, in particular, if and how olfaction affects visual attention. Two experiments are presented in this paper. Firstly, eye tracking is gathered from a number of participants to gain an impression about where and how th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…(v) Heart rate monitor bracelet (see Figure 1(g)): for completeness, QoE should be monitored both using subjective, self-reported, measures, as well as objective ones. Of the latter, the most commonly used are physiological measures [44][45][46][47][48][49]. In this respect, in our study, we chose to monitor the participant's heart rate.…”
Section: Settingmentioning
confidence: 99%
“…(v) Heart rate monitor bracelet (see Figure 1(g)): for completeness, QoE should be monitored both using subjective, self-reported, measures, as well as objective ones. Of the latter, the most commonly used are physiological measures [44][45][46][47][48][49]. In this respect, in our study, we chose to monitor the participant's heart rate.…”
Section: Settingmentioning
confidence: 99%
“…Chen et al [15] performed a study to corroborate this effect and concluded that a multimodal saliency map weighing both visual and olfactory inputs was required. Harvey et al [25] showed that conventional image saliency maps can no longer be relied upon in the same way in olfactory-visual environments and demonstrated a validated model based on empirical findings.…”
Section: Olfactory-visual Interactionsmentioning
confidence: 99%
“…Based on studies carried out by Judauji, J. et al (2012) as well as another study by Morrot, G. et al (2001), both which investigated to what extent visual cues could affect olfactory processing through visual-olfactory associations, deduced that visual cues directly influences odor identification, perception and also attention [21] [51] . Alternatively, studies conducted by Kuang, S. and Zhang, T. (2014) and another by Harvey, C. (2018) examined cross-modal integration in olfactory-visual coupling and found that olfactory cues influence gaze shifts and visual attention finding a functional pathway with which odor stimuli can initiate and guide eye movements [9] [49] [53] . These studies made implications of functional associations between odor and visual pathways but the structural associations were still undiscovered [28] [39] [40] .…”
Section: Iv) Male and Female Unilateral Hemispheric Variances (Left Smentioning
confidence: 99%